PROSPECTS OF IMPROVING INDEPENDENT EDUCATION IN THE HIGHER EDUCATION SYSTEM OF UZBEKISTAN (Intent Research Scientific Journal, 2023)
This paper aims to explore the prospects of improving independent education in the higher education system of Uzbekistan. The study begins by examining the current state of independent learning in the country and identifying the major challenges faced by students and teachers. It then presents a comprehensive analysis of the existing literature on independent learning and its benefits in higher education. Finally, the paper offers a set of recommendations for improving independent learning practices in Uzbekistan, such as the need for pedagogical training for teachers, the development of effective assessment methods, and the provision of support services for students. This paper provides valuable insights into the potential of independent learning to enhance the quality of higher education in Uzbekistan and offers practical solutions for achieving this goal.